(untitled) (Patan Prospective Journal, 2024)
This study explores the radiation shielding properties of Iron-based and Nickel-based alloys with Cobalt composition to evaluate their performance in photon attenuation and shielding applications. The objectives of this work are to determine linear and mass attenuation coefficients (LAC, MAC), half and tenth value layers (HVL, TVL), mean free path (MFP), effective atomic number and electron density (Zeff, Neff), effective conductivity (Ceff), atomic cross section (ACS) and electronic cross section (ECS) of nickel and iron base alloy with Cobalt using Phy-X/PSD within 0.001 MeV to 10 MeV. The result shows Iron and Nickel-based alloys have electron densities around 10²³ electrons per gram, with increased Iron concentration improving low-energy photon attenuation. Nickel-based alloys have a higher MAC and LAC compared to Iron-based oxides, indicating better photon absorption per unit mass and thickness, respectively. Nickel-based alloys exhibit a lower HVL and TVL, indicating greater attenuation and absorption efficiency for photons, especially at lower energies. Conversely, Iron-based alloys, while showing higher HVL and TVL. Nickel-based alloys exhibited higher electron densities the Iron-based alloys and Zeff values for Nickel based alloys, ranging from 27.1 to 27.8 while Iron-based alloys with Zeff between 26.2 and 26.8. Ceff in Iron-based alloys was stable at (1.50 to 1.74) x 10⁹ S/m, while Nickel-based alloys showed significant fluctuations below 0.01 MeV. Nickel-based alloys also had higher ACS and ECS, indicating superior photon interaction, especially at lower energies. These results highlight Nickel based alloys’ greater efficacy in low-energy photon attenuation and the stable performance of Iron based alloys at higher energies.